(untitled) (Global Journals of Research in Engineering, 2011)
Problem -based learning is #x201C;Problem#x201D;......#x201D; based#x201D; ......#x201D;learning#x201D;. Let us look at each of these words. A problem is something that is problematic to the student; something that cannot be resolved with the current level of knowledge and/or way of thinking about the issues. The nature of effective problems in problem-based learning is that they are ill-structured as opposed to well structured. The characteristics of ill-structured problems are that they are real-life and authentic but not teacher#x2019;s exercises, messy not tidy, incomplete in the sense of lacking information needed for their resolution and iterative in the way that they produce further ideas,/hypotheses and learning issues (Barrows 1989; Stephen and Pyke 1977; Margeston 2001). It is vital that the problems are engaging , that they #x201C;smell real#x201D;, are interesting and challenging to students. This engagement stimulates further learning and requires research, elaboration, further analysis and synthesis together with decisions and action plans. The engineering profession requires engineers to deal with uncertainty and solve complex problems of the field, sometimes with incomplete data (Mills Treagust, 2003; NAE, 2004). In addition, engineers need to be able to function as effective members of teams and have strong communication and problem-solving skills (NAE, 2004). However, today#x2019;s engineering graduates lack these skills and have difficulty applying their fundamental knowledge to problems of practice (Mills Treagust, 2003; NAE, 2005; Nguyen, 1998; Vergara, et al., 2009).